Pengaruh Eco-control, Ukuran Perusahaan, dan Environmental Performance Terhadap Pengungkapan Corporate Social Responsibility (Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia periode 2016-2021) - Lutvia Istiqomah; Dirvi Surya Abbas; Imam Hidayat; Sigit Budi Santoso (Pusat Riset dan Inovasi Nasional, 2022)
very company has an obligation to be responsibility for the environment as a form of social care. But in reality, currently many companies in carrying out their activities are not in accordance with the guidelines for corporate social responsibility. Therefore, through environmental control efforts, the size of the company’s total assets, and good environmental performance, it is hoped that the company will be able to increase the tangible form of its obligations from the impact of ongoing operations. This study aims to examine and analyze the effect of eco-control, company size, and environmental performance on the disclosure of corporate social responsibility.The research method uses explanatory research, data collection techniques use secondary data obtained from the annual report. The research sample consisted of 22 manufacturing companies in the food and beverage sub-sector for the 2016-2021 period, the sampling method used was purposive sampling. The results show that eco-control has a positive effect on the disclosure of corporate social responsibility, the size of the company has a negative effect on the disclosure of corporate social responsibility, and environmental performance has a positive effect on the disclosure of corporate social resonsibility. This means that only the eco-control and environmental performance hypotheses are accepted. The ability of eco-control, company size, and environmental performance as independent variables can affect the disclosure of corporate social responsibility by 9.12% and the rest is explained by other factors outside the study.